Association of area-level mortgage discrimination and guideline-concordant non–small cell lung cancer care in the United States. Issue 28 (1st October 2022) - Fan, Qinjin; Hussaini, S. M. Qasim; Pollack, Craig Evan; Yabroff, K. Robin Robin; Nogueira, Leticia M
Abstract : 3 Background: Disparities in receipt of care for non-small cell lung cancer (NSCLC) are well described. Discriminatory mortgage lending, which limits access to home ownership in specific neighborhoods overall and disproportionately for racialized groups, is a marker of systemic racism and lower levels of neighborhood investment. This may, in turn, decrease access to high quality care. We used the mortgage denial rate as a measure of housing discrimination and investigated its association with guideline-concordant NSCLC care. Methods: Mortgage denial rates were estimated at the zip code tabulation areas (ZCTAs) level using the Home Mortgage Disclosure Act (HMDA) database (2014-2019). Mortgage denial rates represent the proportion of denied home loans to total loans and were categorized into quartiles. Individuals ≥ 18 years diagnosed with NSCLC 2014-2019 were identified from the National Cancer Database and combined with HMDA. Multivariable logistic regression models examined associations between mortgage discrimination and receipt of guideline-concordant care, including surgery, chemotherapy, and chemoradiation. A multivariable Cox proportional hazard model examined the association between mortgage discrimination and time to chemotherapy initiation. Results: Cohort included 450, 614 patients newly diagnosed with NSCLC resided in 33, 120 ZCTAs. Individuals residing in ZCTAs with higher mortgage denial rates were more likely to be aged 45-64 years, male, non-Hispanic White, with private health insurance coverage and income < 40, 000/year. 69% of all patients received guideline-concordant care. Likelihood of guideline-concordant care was lower in neighborhoods with higher mortgage denial rates, adjusting for age and sex (Table). This disparity was present in all care subgroups. Time to chemotherapy initiation was longer for patients in neighborhoods with higher mortgage denial rates. Conclusions: Mortgage discrimination is adversely associated with receipt of guideline-concordant NSCLC care. Our examination of institutional practices leading to barriers in access to resources highlights the critical need to understand the pathways through which area-level mortgage denials impact receipt of equitable cancer care.Association of area-level mortgage denial rate and non guideline-concordant NSCLC care. Mortgage denial rates (%) Guideline-concordant treatment (aOR, 95% CI) Surgery (aOR, 95% CI) Chemotherapy (aOR, 95% CI) Chemoradiation (aOR, 95% CI) Time to chemotherapy initiation (aHR, 95% CI) Level 1 (≤15.9) Ref. Ref. Ref. Ref. Ref. Level 2 (16.0-20.5) 1.11 (1.09, 1.13) 1.18 (1.14, 1.20) 1.06 (1.04, 1.07) 1.08 (1.03, 1.13) 1.03 (1.01, 1.05) Level 3 (20.6-25.7) 1.21 (1.18, 1.23) 1.32 (1.27, 1.37) 1.10 (1.08, 1.12) 1.19 (1.13, 1.25) 1.06 (1.04, 1.08) Level 4 (≥25.7) 1.36 (1.34, 1.38) 1.62 (1.55, 1.68) 1.15 (1.30, 1.17) 1.41 (1.33, 1.48) 1.10 (1.08, 1.12)